Efficacy of Intraoperative Neuromonitoring Using Transcranial Motor-Evoked Potentials for Degenerative Cervical Myelopathy: A Prospective Multicenter Study by the Monitoring Committee of the Japanese Society for Spine Surgery and Related Research. Issue 1 (1st January 2022) - Funaba, Masahiro; Kanchiku, Tsukasa; Yoshida, Go; Imagama, Shiro; Kawabata, Shigenori; Fujiwara, Yasushi; Ando, Muneharu; Yamada, Kei; Taniguchi, Shinichirou; Iwasaki, Hiroshi; Tadokoro, Nobuaki; Takahashi, Masahito; et al.
Abstract : Study Design: A prospective multicenter observational study. Objective: To elucidate the efficacy of transcranial motor-evoked potentials (Tc(E)-MEPs) in degenerative cervical myelopathy (DCM) surgery by comparing cervical spondylotic myelopathy (CSM) to cervical ossification of the posterior longitudinal ligament (OPLL) and investigate the timing of Tc(E)-MEPs alerts and types of interventions affecting surgical outcomes. Summary of Background Data: Although CSM and OPLL are the most commonly encountered diseases of DCM, the benefits of Tc(E)-MEPs for DCM remain unclear and comparisons of these two diseases have not yet been conducted. Methods: We examined the results of Tc(E)-MEPs from 1176 DCM cases (840 CSM /336 OPLL) and compared patients background by disease, preoperative motor deficits, and the type of surgical procedure. We also assessed the efficacy of interventions based on Tc(E)-MEPs alerts. Tc(E)-MEPs alerts were defined as an amplitude reduction of more than 70% below the control waveform. Rescue cases were defined as those in which waveform recovery was achieved after interventions in response to alerts and no postoperative paralysis. Results: Overall sensitivity was 57.1%, and sensitivity was higher with OPLL (71.4%) than with CSM (42.9%). The sensitivity of acute onset segmental palsy including C5 palsy was 40% (OPLL/CSM: 66.7%/0%) whereas that of lower limb palsy was 100%. The most common timing of Tc(E)-MEPs alerts was during decompression (63.16%), followed by screw insertion (15.79%). The overall rescue rate was 57.9% (OPLL/CSM: 58.3%/57.1%). Conclusion: Since Tc(E)-MEPs are excellent for detecting long tract injuries, surgeons need to consider appropriate interventions in response to alerts. The detection of acute onset segmental palsy by Tc(E)-MEPs was partially possible with OPLL, but may still be difficult with CSM. The rescue rate was higher than 50% and appropriate interventions may have prevented postoperative neurological complications. Level of Evidence: 3 Abstract : Since transcranial motor-evoked potentials (Tc(E)-MEPs) for degenerative cervical myelopathy are excellent for detecting long tract injuries, surgeons need to consider appropriate interventions in response to Tc(E)-MEPs alerts. The detection of acute onset segmental palsy by Tc(E)-MEPs was partially possible with ossification of the posterior longitudinal ligament, but may still be difficult with cervical spondylotic myelopathy.